Long-term outcome of adult patients with partial anomalous pulmonary venous connection treated surgically and conservatively: data from the SACHER registry and a French center. (25th November 2020) - Touray, M; Bouchardy, J; Ladouceur, M; Schwerzmann, M; Greutmann, M; Tobler, D; Harald, R; Engel, R; Pruvot, E; Blanche, C; Sekarski, N; Rutz, T
Abstract: Introduction: Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital heart disease, which is characterized by one or some but not all pulmonary veins anomalously connected to the right atrium or a systemic vein. PAPVC is either an isolated shunt lesion or associated with an atrial septal defect (ASD). The only curative treatment is surgery, however the indication for surgery can be challenging. This study compares the outcome of patients treated surgically with those clinically monitored. Method: Clinical, surgical, imaging and invasive data were retrospectively reviewed from 7 centers from the Swiss Adult Congenital HEart Registry (SACHER) and a French center. Results: A total of 168 patients with partial anomalous pulmonary venous connection were identified. The majority (77%) of patients underwent surgery and the remaining (23%) were treated conservatively with clinical monitoring. The operated group (OG) had a significantly higher proportion of associated ASD (N=106, 82%) (p<0.001) and a higher prevalence of anomalous pulmonary veins leading to a mean Qp:Qs at 2.5±1.2 before surgery. Latest follow-up was 12 years after surgery. Mean age was 40±17 years. Patients in the non-operated group (NOG) were significantly more dyspneic than the OG (p=0.002). However, the need for medical treatment did not differ between groups: 58% of the NOG and 48% in the OG (p=0.203). Right ventricular (RV) ejection fraction did not differ between groups despite a significantly larger RV end-diastolic volume and a higher Qp:Qs on cardiac magnetic resonance (CMR) in the NOG (table). On echocardiography, the NOG showed a significantly better right ventricular longitudinal function and a higher systolic pulmonary artery pressure than the OG (table). The prevalence of significant valvulopathies did not differ between groups (table). Both groups had normal exercise capacity and with no differences between groups (table). Eighteen (14%) OG patients required a re-intervention either for residual shunt and/or stenosis of the pulmonary veins, superior and inferior vena cava. Conclusion: PAPVC patients after surgical correction, show a favorable outcome in terms of imaging parameters and exercise capacity, however, a significant number presents with symptoms. PAPVC patients treated conservatively with small left to right shunting, have similar outcome justifying a conservative approach. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Unrestricted grant from Actelion, Switzerland